New-Age E-voucher Utility: Redefining Peer-to-Peer Transactions in the Digital Economy - Chirag Naresh Patil; Shilpali Bansu; Manish Ramgopal Soni; Jyotsana Rajendra Parkhedkar (International Journal of Computer Science Languages, 2024)
This system introduces an innovative new-age e-voucher utility designed to facilitate peer-to-peer (P2P) intake through a person-pleasant cell platform. This revolutionary answer empowers people to create and list e-vouchers for numerous services, experiences, or bodily goods, circumventing conventional channels and fostering an extra direct financial machine. Operating on a decentralized architecture, the utility guarantees stable transactions through fee gateways and contains a recognition machine to set up acceptance as true amongst customers. In leveraging the era to attract people, this new-age e-voucher platform pioneers a transforming method of virtual transactions, placing a brand-new popularity for efficiency, security, and comfort inside the evolving panorama of peer-to-peer intake. This groundbreaking new-age e-voucher utility in addition distinguishes itself via way of means of incorporating superior functions and functionalities to decorate the general person experience. The utility consists of integrated compliance functions to deal with ability regulatory demanding situations, incorporating identification verification and adherence to nearby monetary regulations. The recognition machine now no longer the simplest build accepted as true amongst customers; however, it additionally serves as a mechanism for dispute decisions, improving the general reliability of the platform. In phrases of person engagement and network building, the utility introduces social functions, permitting customers to proportion their experiences, advocate services, and hook up with like-minded people. As the new-age e-voucher utility strives to redefine the panorama of virtual transactions, it stands as a complete and revolutionary answer, addressing now no longer the center components of P2P intake but additionally making sure adaptability, security, and personal delight in an ever-evolving virtual ecosystem.
Keywords: P2P (peer-to-peer); digital revolution; dynamic marketplace; e-vouchers (electronic vouchers); sharing economy